Levodopa‐carbidopa intestinal gel: is the naso‐jejunal phase a redundant convention?. Issue 4 (6th April 2018) - Vijiaratnam, Nirosen; Hewer, Sarah; Varley, Sue; Paul, Eldho; Bertram, Kelly L.; Lee, Will; Ligtermoet, Matthew; Williams, David R.
Abstract: Levodopa‐carbidopa intestinal gel (LCIG) is an effective treatment for Parkinson disease. Initiating therapy involves an initial naso‐jejunal (NJ) titration phase. The NJ phase is prolonged with significant morbidity. The aim of this study is to assess the impact of proceeding without the NJ phase on resource utilisation and the outcomes of patients. Twenty‐five patients were started on LCIG using the patients existing levodopa equivalent dose (LED). We recorded change in LED, length of hospital stay, readmission rates and use of outpatient services and clinical outcomes within 6 months. The median length of stay was 4.5 days. Patients had four outpatient clinic reviews and 2.5 community nurse contacts within 6 months. There was no significant change in daily LED on discharge ( P = 0.56). There were significant improvements in all Unified Parkinson Disease Rating Scale subscores ( P < 0.05), the Freezing of Gait scale ( P < 0.01) and Parkinson Disease Quality Of Life 39 score ( P < 0.01). Initiating LCIG without the NJ phase resulted in short admissions, a minimal outpatient burden and no significant requirement for dose titration while producing good clinical outcomes.